Gene–environment interplay in externalizing behavior from childhood through adulthood - Kretschmer, Tina; Vrijen, Charlotte; Nolte, Ilja Maria; Wertz, Jasmin; Hartman, Catharina Annette (Journal of Child Psychology and Psychiatry (and Allied Disciplines), 2022)
Background: Genetic and environmental influences on externalizing problems are often studied separately. Here, we extended prior work by investigating the implications of gene–environment interplay in childhood for early adult externalizing behavior. Genetic nurture would be indicated if parents' genetic predisposition for externalizing behavior operates through the family environment in predicting offspring early adult externalizing behavior. Evocative gene–environment correlation would be indicated if offspring genetic predisposition for externalizing behavior operates through child externalizing behavior in affecting the family environment and later early adult externalizing behavior. Method: Longitudinal data from seven waves of the TRacking Adolescents' Individual Lives Survey, a prospective cohort study of Dutch adolescents followed from age 11 to age 29 (n at baseline = 2,734) were used. Child externalizing behavior was assessed using self and parent reports. Family dysfunction was assessed by parents. Early adult externalizing behavior was assessed using self-reports. Genome-wide polygenic scores for externalizing problems were constructed for mothers, fathers, and offspring. Results: Offspring polygenic score and child behavior each predicted early adult externalizing problems, as did family dysfunction to a small extent. Parents' polygenic scores were not associated with offspring's early adult externalizing behavior. Indirect effect tests indicated that offspring polygenic score was associated with greater family dysfunction via child externalizing behavior (evocative gene–environment correlation) but the effect was just significant and the effect size was very small. Parents' polygenic scores did not predict family dysfunction, thus the data do not provide support for genetic nurture. Conclusions: A very small evocative gene–environment correlation was detected but effect sizes were much more pronounced for stability in externalizing behavior from childhood through early adulthood, which highlights the necessity to intervene early to prevent later problems.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Externalising disorder; family functioning; gene-environment interaction (GxE); longitudinal studies; molecular genetics